IDENTIFIKASI PERTAHANAN DIRI DAN MEKANISME COPING PADA KELAS VII dan VIII SMP 8TANAH PUTIH T.P. 2013/2014 - Wahyuni, Sri Wahyuni Sri; Yakub, Elni Yakub Elni; Asyari, Abu Asyari Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Based on the observations made by the author in the form of scale questionnaire and coping mechanisms of self-defense , then most students do self defense mechanisms and coping types of compensation and set goals . The purpose of this study is :1 ) to determine the description of self-defense mechanisms and coping experienced by students of class VII and VIII SMP 8 Land White . 2 ) To determine the mechanism of self-defense that made ​​the students of class VII and VIII SMP 8 Land White . 3 ) To know the coping mechanisms of the student of class VII and VIII SMP 8 Land White. The method used in this research is descriptive method . The population in this study were students of class VII and VIII SMP . 8 Land White and the sample 50 % of the total population by using a questionnaire . Based on the results of data processing , the description of self defense mechanisms and coping experienced by students over half are in the good category , then a small portion in middle category , then based on the research findings based on those questionnaire that was distributed type - the type of defense mechanism that more students do is type Denial , while coping mechanisms more do students are kind of set goals . Keywords : Self Defense Mechanisms and Coping